Natural Eutectic Solvent Mixture of l‐Menthol/Malonic acid (4 : 1) and Its Ibuprofen Solution: Thermal and Physical Characterizations and NMR Studies of Molecular Interaction. Issue 5 (10th January 2023) - Lázaro‐Rangel, Jehovani M.; Sánchez, Analilia; Inoue, Motomichi; Olivares‐Romero, José Luis; Meza‐Gordillo, Rocío; Salas‐Reyes, Magali; Virués, Claudia; Domínguez, Zaira
Abstract: A eutectic mixture of L ‐menthol and malonic acid, Me /MA (4 : 1), was characterized by calorimetry and other physical measurements. The new deep eutectic solvent (m.p. 6 °C) solvates 338 mg of ibuprofen per mL, and the solution is stable in a wide temperature range. Strategies of NMR titration used in supramolecular chemistry were employed to explore binding forces between the eutectic constituents as well as solute‐solvent interaction in ibuprofen solution. Even in acetonitrile, Me 4 MA is formed through a hydrogen‐bonding network, where the constituents act as hydrogen donors and acceptors at the same time. The estimated association constant is around 30 M −1 ; the binding forces are enough to build the eutectic mixture at high concentrations. The aggregate Me 4 MA forms a molecular complex with ibuprofen in acetonitrile as a result of the cooperative effect of the constituents. In addition, van der Waals interactions are operative between ibuprofen and menthol in the saturated IB ‐Me /MA (4 : 1) solution. Abstract : The type and strength of the non‐covalent interactions that take place in a solution of ibuprofen in a new natural deep eutectic solvent (NADES), based on L ‐menthol, were investigated through NMR methods. Even in acetonitrile, a hydrogen‐bonding network is formed between the components of the solvent. As a result of the cooperative effect of the constituents, a molecular complex is also formed with ibuprofen.